2018
DOI: 10.1021/acsami.8b00685
|View full text |Cite
|
Sign up to set email alerts
|

High-Quality AZO/Au/AZO Sandwich Film with Ultralow Optical Loss and Resistivity for Transparent Flexible Electrodes

Abstract: Transparent flexible electrodes are in ever-growing demand for modern stretchable optoelectronic devices, such as display technologies, solar cells, and smart windows. Such sandwich-film-electrodes deposited on polymer substrates are unattainable because of the low quality of the films, inducing a relatively large optical loss and resistivity as well as a difficulty in elucidating the interference behavior of light. In this article, we report a high-quality AZO/Au/AZO sandwich film with excellent optoelectroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…The ZnS (40 nm)/Ag (10 nm)/TiO x (30 nm) TCE presents the best F value (23.10 À3 W À1 ). This high-level value is comparable to those of the current stateof-the-art [14][15][16][17][18][19][20][21][22][23]. Figure 6 shows the variation of the merit figure and of the sheet resistance as a function of TiO x thickness.…”
Section: Numerical and Experimental Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…The ZnS (40 nm)/Ag (10 nm)/TiO x (30 nm) TCE presents the best F value (23.10 À3 W À1 ). This high-level value is comparable to those of the current stateof-the-art [14][15][16][17][18][19][20][21][22][23]. Figure 6 shows the variation of the merit figure and of the sheet resistance as a function of TiO x thickness.…”
Section: Numerical and Experimental Methodssupporting
confidence: 70%
“…The opto-electrical performances of our electrodes are at the-state-of-the-art of this ETC field [26]. With a fairly large merit figure comparable to literature values [23,[27][28][29], such transparent, conductive three-layer electrodes are good candidates for use as indium-free electrode in organic solar cells.…”
Section: Numerical and Experimental Methodssupporting
confidence: 59%
“…[ 66,73 ] Zhou et al have demonstrated AZO potential after they were able to develop a high‐quality transparent flexible electrode, by designing an AZO/Au/AZO multiple layer structure on a mica substrate. [ 80 ] This thin film (126 nm) exhibited high transmittance percentage (81.7%) and low resistivity.…”
Section: Enabling Technologies For Olaementioning
confidence: 99%
“…For this end, materials with interesting properties for flexible electronics, such as AZO, have been developed. Zhou et al [81] demonstrated that an AZO/Au/AZO layer on mica exhibiting a sheet resistance of 5 Ω/ and a transparency close to 90% for a total layer thickness of 126 nm where the Au layer corresponded to 10 nm. This device withstood a 7 mm bending radius, but its sheet resistance increased to 9 Ω/ while bent to a smaller radius of 5 mm.…”
Section: Amorphous Oxide Conductorsmentioning
confidence: 99%